Arbuscular fungi and mycorrhizae of agricultural soils of the Western Pomerania. Part I. Occurrence of arbuscular fungi and mycorrhizae - Anna Iwaniuk; Janusz Błaszkowski (Acta Mycologica, 2014)
This paper presents results of three-year investigations on the occurrence of arbuscular mycorrhizal fungi and arbuscular mycorrhizae of the phylum Glomeromycota in agricultural soils of the Western Pomerania, north-western Poland. The occurrence of these fungi was determined basing on soil-root mixtures collected from both the field and trap cultures.